The Problematics of The Muslim Community in Responding to The Life Challenges of Modern Society: A Case Study at Muhammadiyah University of Malaysia - Anas Prasetya; Syarifuddin Syarifuddin; Muhammad Rifa Badawi (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Modern society faces multidimensional complexities, ranging from spiritual crises and technological disruption to social inequality. Muslims, with their theological and intellectual capital, are often perceived as suboptimal in responding to these challenges contextually and applicatively. This article aims to analyze the fundamental problems faced by Muslims in formulating answers to the problems of modern society and to explore the strategic role of Islamic higher education institutions, specifically the Muhammadiyah University of Malaysia (UMAM), in bridging this gap. This research uses a qualitative approach with a case study method at UMAM. Data was collected through literature study, observation, and structured interviews with academics and policymakers at UMAM. The findings indicate that the main problems lie in: (1) the dichotomy between naqli and aqli sciences, (2) a static approach to religious texts, and (3) a lack of integrative and innovative solution models. UMAM strives to address these issues through three main strategies: integration of knowledge in the curriculum, problem-based research, and empowering community engagement. This article concludes that UMAM has the potential to become a model social laboratory of Islam that combines the Muhammadiyah renewal ethos with the Malaysian socio-cultural context to produce relevant, humanist, and rahmatan lil 'alamin solutions.